Electrochemical H2O2 Production and Accumulation from H2O by Composite Effect of Al2O3 and BiVO4. Issue 13 (1st January 2019) - Miyase, Yuta; Iguchi, Shoji; Miseki, Yugo; Gunji, Takahiro; Sayama, Kazuhiro
Abstract : The modification effects of both BiVO4 and Al2 O3 on a FTO on efficient oxidative H2 O2 production and accumulation from H2 O were investigated. The initial faradaic efficiency for H2 O2 production (FE (H2 O2 )) reached 95% due to the suppressing influence of direct O2 production via H2 O oxidation on BiVO4 /FTO. Al2 O3 modification suppressed oxidative H2 O2 decomposition to O2, which was confirmed by changes in the I-V curves after H2 O2 addition. The initial FE (H2 O2 ) of Al2 O3 /BiVO4 /FTO modified by chemical vapor deposition (CVD) reached 97%. Oxidative H2 O2 decomposition was significantly suppressed by the loaded Al2 O3, and the amount of accumulated H2 O2 on this composite electrode was reached 7.5 mM at 200 C, which is the highest value in the system for oxidative H2 O2 production from H2 O.